Composite nano-filtration material and preparation method thereof
By introducing nanofiber filter layer and aerogel intercalation meltblown cloth loaded with tea polyphenols into nano-air filter materials, the problems of high filtration resistance and short service life in the prior art are solved, and high-efficiency antibacterial and high-volume dust are achieved The effect of quantity extends service life and improves air quality.
Patent Information
- Application Number
- CN202411789524.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, in particular to a composite nano-filter material and a preparation method thereof. Background Art
[0002] The air quality in a closed environment is closely related to the health and life safety of the people in that environment. Large exhibition venues, hospitals, stations and other large closed environments have a large flow of people. The air in large closed environments needs to be circulated through filtering equipment such as central air conditioners. If there are bacteria, viruses and other pathogens that endanger human health lurking in the air, it will easily cause potential threats of spread and transmission. Conventional nano air filter materials have the problem that the filtration resistance will increase significantly while the filtration efficiency is high. In addition, because the nano air filter materials are thin and light, the filtration resistance will further increase with the increase of use time and dust, resulting in a shorter service life of the filter materials.
[0003] Therefore, there is an urgent need to provide an air filter material that has both excellent antibacterial and antimicrobial properties and a high dust holding capacity. Summary of the invention
[0004] In view of this, the present invention provides a composite nano-filtration material, which has excellent antibacterial and antimicrobial properties, high dust holding capacity and long service life.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] On the one hand, the present invention provides a composite nano-filtration material, comprising a substrate layer and a nanofiber filtration layer loaded on one side of the substrate layer; the nanofiber filtration layer is composed of nanofibers loaded with tea polyphenols, and the nanofibers loaded with tea polyphenols include the following components in mass percentage: 1-50% tea polyphenols and 50-99% nanocellulose.
[0007] Preferably, the surface density of the substrate layer is 20-200 g / m 2 The surface density of the nanofiber filter layer is 0.05-5g / m 2 .
[0008] Preferably, the substrate layer is an aerogel intercalated meltblown cloth.
[0009] Preferably, the aerogel intercalated melt-blown cloth comprises an aerogel mixture and a melt-blown cloth, and the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is ≥5%.
[0010] Preferably, the aerogel mixture is aerogel or a mixture of aerogel and hot melt adhesive;
[0011] When the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is 5-30%, the aerogel mixture is aerogel;
[0012] When the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is greater than 30%, the aerogel mixture is a mixture of aerogel and hot melt adhesive, and the volume ratio of the aerogel to the hot melt adhesive is 1:0.2-2.
[0013] Preferably, the aerogel includes one or more of silica aerogel, graphene aerogel, carbon or carbide aerogel, organic aerogel, cellulose aerogel, and starch aerogel.
[0014] Preferably, the hot melt adhesive includes one or more of ethylene-vinyl acetate copolymer hot melt adhesive, polyurethane hot melt adhesive, and polyurethane hot melt adhesive.
[0015] Preferably, the diameter of the nanofibers loaded with tea polyphenols is 100-1000 nm.
[0016] Preferably, the thickness of the composite nano-filtration material is 0.1-2 cm, and the thickness of the nanofiber filtration layer is at least 10% of the thickness of the composite nano-filtration material.
[0017] Preferably, the nanocellulose comprises one or more of nanocellulose extracted from trees or natural cellulose fibers, nanocellulose whiskers, bacterial cellulose, microfibrillated nanocellulose, and super-strength nanocellulose.
[0018] On the other hand, the present invention also provides a method for preparing the composite nano-filtration material described in any one of the above, comprising the following steps:
[0019] (1) dissolving tea polyphenol powder in a first solvent to obtain a first spinning solution;
[0020] (2) dissolving the nanocellulose in a second solvent to obtain a second spinning solution;
[0021] (3) mixing the first spinning solution and the second spinning solution to obtain a mixed spinning solution;
[0022] (4) The mixed spinning solution is sprayed onto the substrate layer by an electrospinning machine, and subjected to a curing treatment to obtain a composite nano-filtration material.
[0023] Preferably, the mass content of tea polyphenols in the first spinning solution is 8-25%.
[0024] Preferably, the particle size of the tea polyphenol powder is ≤2 μm.
[0025] Preferably, the mass content of nanocellulose in the second spinning solution is 5-35%.
[0026] Preferably, the nanocellulose has a diameter of 1-100 nm and a length of 10-300 nm.
[0027] Preferably, the first solvent includes one or more of dimethylformamide, ethanol, dichloromethane, and dimethylformamide.
[0028] Preferably, the second solvent includes one or more of dimethylformamide, dimethylformamide, dimethyl sulfoxide, ionic liquid, N-methylpyrrolidone, dichloromethane, chloroform, and acetic acid.
[0029] The composite nano-filtration material of the embodiment of the present invention has the following beneficial effects compared with the prior art:
[0030] The composite nano-filter material of the present invention has antibacterial and antifungal effects throughout its life cycle and has the function of removing odors. It uses tea polyphenols as antibacterial components and can be extracted from various types of tea. It is easy to obtain, low in cost, and green and environmentally friendly. In addition, by compounding the nanofiber filter layer with the substrate layer, the dust holding capacity of the composite nano-filter material can be effectively improved and the service life of the filter material can be extended. The composite nano-filter material of the present invention can be widely used in filtering equipment in closed environments such as hospitals, stations, high-speed rail stations, and large venues, effectively improving the air quality in closed environments. DETAILED DESCRIPTION
[0031] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0032] In one aspect of the present invention, the present invention proposes a composite nano-filtration material, comprising a substrate layer and a nanofiber filtration layer loaded on one side of the substrate layer; the nanofiber filtration layer is composed of nanofibers loaded with tea polyphenols, and the nanofibers loaded with tea polyphenols include the following components in percentage by mass: 1-50% tea polyphenols and 50-99% nanocellulose. Among them, the tea polyphenols can be, for example, 1%, 5%, 10%, 20%, 30%, 40%, 50%, etc., and the nanocellulose can be, for example, 99%, 95%, 90%, 80%, 70%, 60%, 50%, etc. Among them, the higher the content of tea polyphenols, the better the antibacterial performance, but if the content of tea polyphenols is too high, for example, it is difficult to spin uniform nanofibers after exceeding 50%.
[0033] The composite nano-filtration material of the present invention has antibacterial and antimicrobial effects throughout its life cycle and has the function of removing odors. It uses tea polyphenols as antibacterial components and can be extracted from various types of tea. It is easy to obtain, low in cost, and environmentally friendly.
[0034] In some embodiments of the present invention, the diameter of the nanofiber loaded with tea polyphenols is 100-1000nm, for example, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, etc. The smaller the diameter of the nanofiber loaded with tea polyphenols, the higher the filtration efficiency, but at the same time the filtration resistance will also increase, and the smaller the diameter of the nanofiber loaded with tea polyphenols, the larger the specific surface area of the nanofiltration material, so that the antibacterial performance is better.
[0035] In some embodiments of the present invention, the thickness of the composite nano-filter material is 0.1-2 cm, for example, 0.1 cm, 0.2 cm, 0.3 cm, 0.5 cm, 1 cm, 2 cm, etc.; the thickness of the nano-fiber filter layer is at least 10% of the thickness of the composite nano-filter material, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc. The greater the thickness of the nano-fiber filter layer and the thickness of the composite nano-filter material, the greater the dust holding capacity, and the product life cycle will be increased when used as a filter element, which can be adjusted according to actual conditions.
[0036] In some embodiments of the present invention, the surface density of the substrate layer is 20-200 g / m 2 , for example, it can be 20g / m 2 , 30g / m 2 , 40g / m 2 , 50g / m 2 , 80g / m 2 , 100g / m 2 , 200g / m 2 wait.
[0037] In some embodiments of the present invention, the surface density of the nanofiber filtration layer is 0.05-5 g / m 2 , preferably 1.0-2.5g / m 2 , for example, it can be 0.05g / m 2 , 0.5g / m 2 , 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 , 3g / m 2 , 4g / m2 , 5g / m 2 Under the gram weight distribution condition, the nanofiber filter layer can obtain a composite nano-filter material with excellent filtration resistance and filtration efficiency.
[0038] In some embodiments of the present invention, the nanocellulose includes one or more of nanocellulose extracted from trees or natural cellulose fibers, nanocellulose whiskers, bacterial cellulose, microfibrillated nanocellulose, and super-strength nanocellulose.
[0039] In some embodiments of the present invention, the substrate layer is an aerogel intercalated meltblown cloth, and the aerogel intercalated meltblown cloth is prepared by directly spraying preheated aerogel and a mixture thereof into meltblown fibers in a meltblown production line. At an air flow rate of 32 L / min, the filtration resistance of the substrate layer to 0.3 μm NaCl or KCl is less than 10 Pa, and the breaking strength is ≥ 15 N. As the air flow rate increases, the filtration resistance decreases accordingly.
[0040] Aerogel has a significant adsorption effect due to its light weight, large specific surface area and porous structure. The present invention adopts aerogel intercalated meltblown cloth as the substrate layer, which can effectively enhance the dust holding capacity of the composite nano-filter material, improve the filtration efficiency of the composite nano-filter material, and make up for the problem of small dust holding capacity of the nanofiber filter layer.
[0041] In some embodiments of the present invention, the aerogel intercalated melt-blown cloth comprises an aerogel mixture and a melt-blown cloth, and the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is ≥5%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. The aerogel content will affect the dust holding capacity of the composite nano-filtration material, and further affect its service life. The higher the aerogel content, the fluffier the aerogel intercalated melt-blown cloth, the higher the filtration efficiency, and the higher the dust holding capacity.
[0042] In some embodiments of the present invention, the aerogel mixture is a mixture of aerogel or aerogel and hot melt adhesive; when the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is 5-30%, the aerogel mixture is aerogel; and when the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is greater than 30%, the aerogel mixture is a mixture of aerogel and hot melt adhesive, and the volume ratio of the aerogel to the hot melt adhesive is 1:0.2-2, for example, 1:0.2, 1:0.5, 1:1, 1:1.5, 1:2, etc. The increase of hot melt adhesive will relatively reduce the content of aerosol, and thus relatively reduce the dust holding capacity of the composite nano-filtration material.
[0043] In some embodiments of the present invention, the aerogel includes one or more of silica aerogel, graphene aerogel, carbon or carbide aerogel, organic aerogel, cellulose aerogel, and starch aerogel. The aerogel is in a powder state, and the aerogel powder can have a micropore diameter, for example, less than 2nm, a mesopore diameter, for example, 2-500nm, a mesopore diameter, for example, 500-1500nm, or a combination of multiple pore diameters. Specifically, the smaller the pore diameter of the aerogel powder, the higher the filtration efficiency of the aerogel intercalated meltblown cloth, but at the same time, the air resistance will increase relatively and the dust holding capacity will decrease. The particle size of the aerogel powder can be determined according to actual conditions.
[0044] In some embodiments of the present invention, the hot melt adhesive includes one or more of ethylene-vinyl acetate copolymer hot melt adhesive, polyurethane hot melt adhesive, and polyurethane hot melt adhesive. The hot melt adhesive is in powder form, and the pore size of the hot melt adhesive powder is not particularly limited.
[0045] In some embodiments of the present invention, the aerogel intercalated meltblown cloth can be prepared by the following method: in the process of online production of meltblown cloth, when the meltblown spinneret has not reached the receiving component (receiving roller or receiving mesh curtain), the aerogel nozzle component is 3-50cm away from the meltblown spinneret fiber, and the airflow directly blows the aerogel or a mixture of aerogel and hot melt adhesive (the aerogel or a mixture of aerogel and hot melt adhesive needs to be preheated to 80-100°C in advance) between the ultrafine fibers of the meltblown. The angle between the airflow and the meltblown fiber is 45-90°, preferably 60-85°, the air flow rate is not more than 150m / s, preferably less than 100m / s, and the position of blowing into the meltblown fiber is controlled at 2-10cm from the surface of the receiving component.
[0046] In the aerogel intercalated meltblown cloth, because aerogel is a porous material, the specific surface area is several orders of magnitude larger than that of conventional meltblown cloth, so the adsorption performance of dust and other particulate matter is significantly improved. This is mainly reflected in the dust holding capacity of aerogel meltblown cloth being 2-10 times higher than that of conventional meltblown cloth. The increased dust holding capacity will significantly increase its service life when used as an air filter element.
[0047] The composite nano-filtration material prepared in the embodiment of the present invention has a full-life cycle antibacterial and antimicrobial effect on Escherichia coli, Staphylococcus aureus, etc., and achieves high dust holding capacity and efficient filtration effect under low filtration resistance through the nano-fiber molecular sieve filtration principle and porous aerogel physical adsorption. When the filtration resistance is lower than 20Pa, the filtration efficiency for oily dioctyl phthalate (DOP) particles of 0.01-0.03μm and above and saline NaCl and KCl particles can reach 90-100%, and can be widely used in central air conditioners and various air filters.
[0048] In another aspect of the present invention, the present invention provides a method for preparing the composite nanofiltration material described in any one of the above, comprising the following steps:
[0049] (1) Dissolving tea polyphenol powder in a first solvent to obtain a first spinning solution.
[0050] In some embodiments of the present invention, the particle size of the tea polyphenol powder is ≤ 2 μm to facilitate dissolution.
[0051] In some embodiments of the present invention, the mass content of tea polyphenols in the first spinning solution is 8-25%, for example, 8%, 10%, 15%, 20%, 25%, etc. Tea polyphenols serve as the main antibacterial component of the composite nanofiltration material.
[0052] In some embodiments of the present invention, the first solvent includes one or more of dimethylformamide, ethanol, dichloromethane, and dimethylformamide; wherein the dissolution is stirring dissolution at room temperature, which is not particularly limited.
[0053] (2) Dissolving the nanocellulose in a second solvent to obtain a second spinning solution.
[0054] In some embodiments of the present invention, the diameter of the nanocellulose is 1-100 nm, for example, it can be 1 nm, 3 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 100 nm, etc.; the length of the nanocellulose is 10-300 nm, for example, it can be 10 nm, 20 nm, 50 nm, 100 nm, 120 nm, 130 nm, 150 nm, 180 nm, 200 nm, 250 nm, 300 nm, etc.
[0055] In some embodiments of the present invention, the mass content of nanocellulose in the second spinning solution is 5-35%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, etc.; the second solvent includes one or more of dimethylformamide, dimethylformamide, dimethyl sulfoxide, ionic liquid, N-methylpyrrolidone, dichloromethane, chloroform, and acetic acid. The higher the mass content of nanocellulose, the greater the concentration of the second spinning solution, and the thicker the diameter of the spun nanofibers under the same other conditions. If the content exceeds 35%, normal spinning is impossible.
[0056] In some embodiments of the present invention, the dissolution is heated and stirred dissolution, the heating and stirring temperature is 20-90°C, for example, 20°C, 50°C, 70°C, 90°C, etc., and the time is 1-20h, for example, 1h, 5h, 10h, 15h, 20h, etc. There is no special limitation on this, as long as it can be dissolved, it can be adjusted according to actual conditions.
[0057] (3) Mixing the first spinning solution and the second spinning solution to obtain a mixed spinning solution, and temporarily storing the mixed spinning solution in a liquid storage device.
[0058] In some embodiments of the present invention, mixing is performed by heating and stirring at 20-90° C. until the mixture is uniformly mixed. After mixing, defoaming treatment is performed according to actual conditions. Both mixing and defoaming are conventional methods and are not particularly limited.
[0059] (4) The mixed spinning solution is sprayed onto the substrate layer by an electrospinning machine, and subjected to a curing treatment to obtain a composite nano-filtration material.
[0060] The specific step is: the mixed spinning solution is slid from the spinning block of the electrospinning machine and coated on the spinning line, and is sprayed perpendicularly to the substrate layer to the online input substrate layer under the Coulomb force of the high-voltage electric field, and is cured to obtain a composite nano-filtration material.
[0061] In some embodiments of the present invention, the electrospinning machine can be a needle-free electrospinning machine, and the mixed spinning solution is sprayed onto the substrate layer under the action of the 30KV-60KV high voltage electric field of the electrospinning machine. The spinning voltage is set according to the electrospinning surface density. The larger the surface density, the higher the spinning voltage. The preferred spinning voltage is 35KV-45KV; the moving speed of the spinning block is 0.5-30m / s, preferably 2-15m / s. The faster the moving speed of the spinning block, the less the amount of spinning solution applied to the spinning line per unit time, and the smaller the gram weight of the obtained nanofiber layer. ; The spinning line setting is mainly based on the electrospinning machine setting, preferably 10-30 lines; the output speed of the substrate layer is 0.2-10m / s, preferably 0.6-3m / s, the greater the substrate output speed, the shorter the receiving spinning time, and the smaller the weight of the obtained nanofiber filter layer; the injection direction is perpendicular to the movement direction of the substrate layer, and the receiving distance is 15-50cm, preferably 20-35cm. The smaller the receiving distance, the insufficient evaporation of the solvent, and the higher the fineness of the obtained fiber. The greater the receiving distance, the finer the obtained nanofiber, but at the same time, the spinning voltage needs to be increased.
[0062] In some embodiments of the present invention, the curing treatment includes drying and hot rolling, wherein the drying can be carried out at 60-90°C for 5-20 minutes, and the drying temperature can be, for example, 60°C, 70°C, 80°C, 90°C, etc., preferably exceeding the boiling point of the solvent, and the drying time is based on the complete volatilization of the electrospinning solvent, without special limitation; hot rolling can be hot rolling with hot rollers, and hot rolling is based on effective bonding between the substrate and the nanofiber composite layer, and the tear strength is preferably greater than 15N, and the pressurization is based on not destroying the substrate web structure. For example, the polypropylene meltblown cloth does not exceed 120°C under pressure, and does not exceed 80°C under no pressure. It is a conventional treatment method and is not specifically limited.
[0063] The preparation method of the composite nano-filter material of the invention is simple and has high production efficiency, and can be produced on a large scale.
[0064] Example 1
[0065] This embodiment discloses a composite nanofiltration material, and its preparation method is as follows:
[0066] (1) dissolving tea polyphenol powder with a particle size of 1.5 μm in N,N-dimethylacetamide to obtain a tea polyphenol (AP) solution with a mass content of 8%;
[0067] (2) dissolving nanocellulose crystals (CNC) with a diameter of 2-5 nm and a length of 200 nm in N,N-dimethylformamide, stirring continuously at 25° C. for 1 h, to obtain a nanocellulose solution with a mass content of 12%;
[0068] (3) mixing the tea polyphenol solution and the nanocellulose solution in a ratio of 1:9 at 25° C. with continuous stirring, and obtaining a CNC / AP spinning solution after defoaming;
[0069] (4) The CNC / AP spinning stock solution was added to the liquid reservoir, and under the action of the 35KV high voltage electric field of the needleless electrospinning machine, it was directly sprayed and received into the substrate layer transmitted online. The spinning block moving speed was 1m / s, there were 20 spinning lines, the substrate conveying speed was 0.8m / s, the receiving distance was 20cm, the average diameter of the nanofibers in the nanofiber filter layer was 600nm, and the total amount of the nanofiber filter layer was controlled at 1.1g / m 2 ;
[0070] (5) The substrate layer carries the nanofiber filter layer out of the high voltage electric field, is dried at 70° C. for 10 min, and then is hot-pressed by a hot roller at 75° C. to obtain a composite nano-filter material.
[0071] In this embodiment, the filtration resistance is 5Pa, the aerogel content is 30% (the aerogel pore size is 20nm, the volume ratio of aerogel to polyurethane hot melt adhesive is 1:1.2, and the preheating temperature is 90°C), and the gram weight is 25g / m 2 The cellulose aerogel intercalated meltblown cloth is used as the substrate layer, and the surface density of the prepared CNC / AP composite nanofiltration material is 26.1g / m 2 ; Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is tested to be 98.9%, and the filtration resistance is 18.9Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.9%, and the filtration resistance is 15.8Pa; according to the national standard GB / T14295-2019, the dust holding capacity reaches 135g / m 3According to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, the results showed that there were no obvious colonies of multiple bacteria species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli, and the antibacterial rate reached 86.3%, with excellent antibacterial and antibacterial effects.
[0072] Example 2
[0073] This embodiment discloses a composite nanofiltration material, and its preparation method is as follows:
[0074] (1) dissolving tea polyphenol powder with a particle size of 2 μm in a solvent (N,N-dimethylacetamide:acetone=4:1) to obtain a tea polyphenol (AP) solution with a mass content of 9%;
[0075] (2) dissolving cellulose nanofibers (CNF) with a diameter of 5-10 nm and a length of 150 nm in a solvent (N,N-dimethylacetamide:acetone = 4:1), stirring continuously at 25° C. for 4 h, and obtaining a nanocellulose solution with a mass content of 12%;
[0076] (3) mixing the tea polyphenol solution and the nanocellulose solution in a ratio of 2:8 at 25° C. and continuously stirring to obtain a CNF / AP spinning solution after defoaming;
[0077] (4) The CNF / AP spinning stock solution was added to the liquid reservoir, and under the action of the 35KV high voltage electric field of the needleless electrospinning machine, it was directly sprayed and received into the substrate layer transmitted online. The spinning block moving speed was 2.5m / s, there were 20 spinning lines, the substrate conveying speed was 1m / s, the receiving distance was 22cm, the average diameter of the nanofibers in the nanofiber filter layer was 500nm, and the total amount of the nanofiber filter layer was controlled at 1.5g / m 2 ;
[0078] (5) The substrate layer carries the nanofiber filter layer out of the high voltage electric field, is dried at 80° C. for 20 min, and then is hot-pressed by a hot roller to obtain a composite nano-filter material.
[0079] In this embodiment, the filtration resistance is 5.2Pa, the aerogel content is 30% (the aerogel pore size is 15nm, the volume ratio of aerogel to polyurethane hot melt adhesive is 1:1.2, and the preheating temperature is 95°C), and the gram weight is 30g / m 2 The cellulose aerogel intercalated meltblown cloth is used as the substrate layer, and the surface density of the prepared CNF / AP composite nanofiltration material is 26.5g / m 2; Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is tested to be 99.93%, and the filtration resistance is 14.6Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.89%, and the filtration resistance is 12.6Pa; according to the national standard GB / T14295-2019, the dust holding capacity reaches 142g / m 3 According to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, the results showed that there were no obvious colonies of multiple bacteria such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli, and the antibacterial rate reached 80%, with excellent antibacterial effect.
[0080] Example 3
[0081] This embodiment discloses a composite nanofiltration material, and its preparation method is as follows:
[0082] (1) dissolving tea polyphenol powder with a particle size of 1.5 μm in N,N-dimethylformamide solvent to obtain a tea polyphenol (AP) solution with a mass content of 9%;
[0083] (2) dissolving microfibrillated nanocellulose (MFC) with a diameter of 1-2 nm and a length of 80 nm in an ionic liquid, stirring continuously at 35° C. for 4 h, and obtaining a nanocellulose solution with a mass content of 11%;
[0084] (3) mixing the tea polyphenol solution and the nanocellulose solution in a ratio of 2:8 at 25° C. and stirring continuously to obtain the MFC / AP spinning solution after defoaming;
[0085] (4) The MFC / AP spinning stock solution was added to the liquid reservoir, and under the action of the 45KV high voltage electric field of the needleless electrospinning machine, it was directly sprayed and received into the substrate layer transmitted online. The spinning block moving speed was 2.5m / s, there were 20 spinning lines, the substrate conveying speed was 1.5m / s, the receiving distance was 18cm, the average diameter of the nanofibers in the nanofiber filter layer was 500nm, and the total amount of the nanofiber filter layer was controlled at 1.8g / m 2 ;
[0086] (5) The substrate layer carries the nanofiber filter layer out of the high voltage electric field, is dried at 65° C. for 15 min, and then is hot-pressed by a hot roller to obtain a composite nano-filter material.
[0087] In this embodiment, the filtration resistance is 3.5 Pa, the aerogel content is 40% (the aerogel pore size is 5 nm, the volume ratio of aerogel to polyurethane hot melt adhesive is 1:1.5, and the preheating temperature is 90°C), and the gram weight is 40g / m 2The cellulose aerogel intercalated meltblown cloth is used as the substrate layer, and the surface density of the prepared MFC / AP composite nanofiltration material is 41.8g / m 2 ; Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is tested to be 99.99%, and the filtration resistance is 18.4Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.93%, and the filtration resistance is 16.7Pa; according to the national standard GB / T14295-2019, the dust holding capacity reaches 141g / m 3 According to the oscillation test method in ASTM E2149 and GB / T20944.2-2008 standards, the negative Staphylococcus aureus, positive Staphylococcus aureus, Escherichia coli and other bacteria were tested without obvious colonies, and the antibacterial rate reached 84.7%, with excellent antibacterial effect.
[0088] Example 4
[0089] This embodiment discloses a composite nanofiltration material, and its preparation method is as follows:
[0090] (1) dissolving tea polyphenol powder with a particle size of 1.8 μm in a solvent (N,N-dimethylacetamide: dimethyl sulfoxide = 3:1) to obtain a tea polyphenol (AP) solution with a mass content of 10%;
[0091] (2) dissolving cellulose nanofiber (CNF) powder with a diameter of 10-15 nm and a length of 150 nm in a solvent (N,N-dimethylacetamide: dimethyl sulfoxide = 3:1) and stirring at 30°C for 2 h to obtain a nanocellulose solution with a mass content of 11%;
[0092] (3) mixing the tea polyphenol solution and the nanocellulose solution in a ratio of 3:7 at 30° C. with continuous stirring, and obtaining a CNF / AP spinning solution after defoaming;
[0093] (4) The CNF / AP spinning stock solution was added to the liquid reservoir, and under the action of the 45KV high voltage electric field of the needleless electrospinning machine, it was directly sprayed and received into the substrate layer transmitted online. The spinning block moving speed was 3.5m / s, there were 20 spinning lines, the substrate conveying speed was 2m / s, the receiving distance was 15cm, the average diameter of the nanofibers in the nanofiber filter layer was 700nm, and the total amount of the nanofiber filter layer was controlled at 2.5g / m 2 ;
[0094] (5) The substrate layer carries the nanofiber filter layer out of the high voltage electric field, is dried at 60° C. for 15 min, and then is hot-pressed by a hot roller to obtain a composite nano-filter material.
[0095] In this embodiment, the filtration resistance is 5Pa, the aerogel content is 32% (the aerogel pore size is 5nm, the volume ratio of aerogel to polyurethane hot melt adhesive is 1:0.6, and the preheating temperature is 80°C), and the gram weight is 50g / m 2 The cellulose aerogel intercalated meltblown cloth is used as the substrate layer, and the surface density of the prepared CNF / AP antibacterial high-filtration and low-resistance nano air filter material is 52.5g / m 2 ; Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the test showed that the filtration efficiency of 0.075um saline NaCl was 99.99%, and the filtration resistance was 17.6Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.95%, and the filtration resistance is 16.5Pa; according to the national standard GB / T14295-2019, the dust holding capacity reaches 139g / m 3 According to the oscillation test method in ASTM E2149 and GB / T20944.2-2008 standards, the negative Staphylococcus aureus, positive Staphylococcus aureus, Escherichia coli and other bacteria were tested without obvious colonies, and the antibacterial rate reached 85.7%, with excellent antibacterial effect.
[0096] Example 5
[0097] This embodiment is basically the same as embodiment 1, except that in step (4), the spinning voltage is 42 kV, the spinning block moving speed is 3.5 m / s, the substrate conveying speed is 2 m / s, and the average diameter of the nanofibers in the obtained nanofiber filter layer is 500 nm and the gram weight is 2.0 g / m 2 .
[0098] The surface density of the prepared CNC / AP composite nanofiltration material is 27.0 g / m 2 Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is tested to be 99.19%, and the filtration resistance is 19.2Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.93%, and the filtration resistance is 17.4Pa. According to the national standard GB / T14295-2019, the dust holding capacity reaches 132g / m 3 According to the oscillation test method in ASTM E2149 and GB / T20944.2-2008 standards, there were no obvious colonies in multiple bacterial species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli, and the antibacterial rate reached 87.1%, with excellent antibacterial effect.
[0099] Example 6
[0100] This embodiment is basically the same as the embodiment 1, the only difference being that in step (3), the tea polyphenol solution and the nanocellulose solution are mixed in a ratio of 3:7.
[0101] Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is tested to be 90.3%, and the filtration resistance is 19.1Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.95%, and the filtration resistance is 16.8Pa. According to the national standard GB / T14295-2019, the dust holding capacity reaches 132g / m 3 According to the oscillation test method in ASTME2149 and GB / T 20944.2-2008 standards, the negative Staphylococcus aureus, positive Staphylococcus aureus, Escherichia coli and other bacteria were tested without obvious colonies, and the antibacterial rate reached 89.7%, with excellent antibacterial effect.
[0102] Example 7
[0103] This embodiment is basically the same as embodiment 2, the only difference is that the filtration resistance is 5Pa, the aerogel content is 40% (wherein the aerogel pore size is 5nm, the aerogel and polyurethane aerogel mixing volume ratio is 1:1.5, and the preheating temperature is 90°C), and the gram weight is 40g / m 2 The cellulose aerogel intercalated meltblown cloth is the substrate layer.
[0104] The surface density of the prepared CNF / AP composite nanofiltration material is 41.5 g / m 2 m, using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the test showed that the filtration efficiency of 0.075um saline NaCl was 99.9995%, the filtration resistance was 19.8Pa, and the filtration efficiency of 0.08-2.5um DOP oily particles was over 99.95%, the filtration resistance was 18.7Pa, and the dust holding capacity was increased by 28%; according to the national standard GB / T14295-2019, the dust holding capacity reached 155g / m 3 According to the oscillation test method in ASTM E2149 and GB / T20944.2-2008 standards, the negative Staphylococcus aureus, positive Staphylococcus aureus, Escherichia coli and other bacterial species showed no obvious colonies, and the antibacterial rate reached 80.7%, with excellent antibacterial effect.
[0105] Comparative Example 1
[0106] This comparative example is basically the same as Example 1, the only difference being that the substrate selected has a filtration resistance of 5 Pa and a gram weight of 25 g / m 2 Conventional meltblown cloth.
[0107] The surface density of the CNC / AP composite nanofiltration material prepared in this comparative example is 26.1 g / m 2 ; Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is tested to be 95.6%, and the filtration resistance is 18.9Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 96.1%, and the filtration resistance is 15.8Pa; according to the national standard GB / T14295-2019, the dust holding capacity reaches 35g / m 3 According to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, the negative Staphylococcus aureus, positive Staphylococcus aureus, Escherichia coli and other bacteria were tested without obvious colonies, and the antibacterial rate reached to 86.3% , with excellent antibacterial and antibacterial effects.
[0108] Comparative Example 2
[0109] This comparative example is basically the same as Example 1, the difference being only in step (1).
[0110] (1) dissolving tea polyphenol powder with a particle size of 1.5 μm in N,N-dimethylacetamide to obtain a tea polyphenol (AP) solution with a mass content of 51%;
[0111] This comparative example cannot be electrospun normally because the main cellulose fiber content is too low.
[0112] Comparative Example 3
[0113] This comparative example is basically the same as Example 1, the difference being only in step (4).
[0114] (4) The CNC / AP spinning stock solution was added to the liquid reservoir, and under the action of the 55KV high-voltage electric field of the needle-free electrospinning machine, it was directly sprayed and received into the substrate layer transmitted online. The spinning block moved at a speed of 35m / s, there were 20 spinning lines, the substrate conveying speed was 4m / s, and the receiving distance was 20cm. Because the substrate transmission speed was too fast, the electrospinning speed could not match, and the nanofiltration layer could not be prepared normally.
[0115] Comparative Example 4
[0116] This comparative example is basically the same as Example 2, the difference being only in steps (1) and (4).
[0117] (1) dissolving tea polyphenol powder with a particle size of 2 μm in a solvent (N,N-dimethylacetamide:acetone=4:1) to obtain a tea polyphenol (AP) solution with a mass content of 4%;
[0118] (4) The CNF / AP spinning stock solution was added to the liquid reservoir, and under the action of the 55KV high voltage electric field of the needleless electrospinning machine, it was directly sprayed and received into the substrate layer transmitted online. The spinning block moving speed was 5m / s, there were 20 spinning lines, the substrate conveying speed was 0.2m / s, the receiving distance was 5cm, the average diameter of the nanofibers in the nanofiber filter layer was 1200nm, and the square gram weight of the nanofiber filter layer was 5g / m 2 ;
[0119] The surface density of the CNF / AP composite nanofiltration material prepared in this comparative example is 30.0 g / m 2 ; Using TSI8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl is 100%, and the filtration resistance is 76.2Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach 100%, and the filtration resistance is 54.3Pa; according to the national standard GB / T14295-2019, the dust holding capacity reaches 62g / m 3 ; The design goal of low filtration resistance under high filtration efficiency cannot be achieved, and the dust holding capacity is significantly reduced.
[0120] In summary, the present invention prepares a nanofiber filter layer loaded with tea polyphenols by electrospinning technology, and composites it online on a substrate layer, so as to prepare a high-filtration and low-resistance air filter material with full life cycle antibacterial and bacteriostatic properties in one step. The filter material has the advantages of low filtration resistance, high filtration efficiency, full life cycle antibacterial and bacteriostatic properties, less materials, low cost, simple preparation process, etc. It can achieve efficient filtration of oily and saline fine particles, has a significant effect on protecting human health in a closed environment, can be widely used in antibacterial and antibacterial air filters in large, medium and small closed environments, and can also be used alone as an additional antibacterial filter for central air conditioning.
[0121] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite nano-filtration material, characterized in that: It includes a substrate layer and a nanofiber filter layer supported on one side of the substrate layer; The nanofiber filter layer is composed of nanofibers loaded with tea polyphenols, and the nanofibers loaded with tea polyphenols include the following components in percentage by mass: 1-50% tea polyphenols and 50-99% nanocellulose.
2. The composite nanofiltration material according to claim 1, characterized in that: The surface density of the substrate layer is 20-200 g / m 2 The surface density of the nanofiber filter layer is 0.05-5g / m 2 .
3. The composite nanofiltration material according to claim 1, characterized in that: The substrate layer is an aerogel intercalated meltblown cloth; The aerogel intercalated melt-blown cloth comprises an aerogel mixture and a melt-blown cloth, and the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is ≥5%.
4. The composite nano-filtration material according to claim 3, characterized in that: The aerogel mixture is aerogel or a mixture of aerogel and hot melt adhesive; When the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is 5-30%, the aerogel mixture is aerogel; When the mass content of the aerogel mixture in the aerogel intercalated melt-blown cloth is greater than 30%, the aerogel mixture is a mixture of aerogel and hot melt adhesive, and the volume ratio of the aerogel to the hot melt adhesive is 1:0.2-2.
5. The composite nano-filtration material according to claim 4, characterized in that: The aerogel includes one or more of silica aerogel, graphene aerogel, carbon or carbide aerogel, organic aerogel, cellulose aerogel, and starch aerogel; The hot melt adhesive includes one or more of ethylene-vinyl acetate copolymer hot melt adhesive, polyurethane hot melt adhesive, and polyurethane hot melt adhesive.
6. The composite nanofiltration material according to claim 1, characterized in that: The diameter of the nanofiber loaded with tea polyphenols is 100-1000nm.
7. A method for preparing the composite nanofiltration material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) dissolving tea polyphenol powder in a first solvent to obtain a first spinning solution; (2) dissolving the nanocellulose in a second solvent to obtain a second spinning solution; (3) mixing the first spinning solution and the second spinning solution to obtain a mixed spinning solution; (4) The mixed spinning solution is sprayed onto the substrate layer by an electrospinning machine, and subjected to a curing treatment to obtain a composite nano-filtration material.
8. The method for preparing the composite nano-filtration material according to claim 7, characterized in that: The mass content of tea polyphenols in the first spinning solution is 8-25%; The particle size of the tea polyphenol powder is ≤2 μm.
9. The method for preparing the composite nano-filtration material according to claim 7, characterized in that: The mass content of nanocellulose in the second spinning solution is 5-35%; The diameter of the nanocellulose is 1-100 nm and the length is 10-300 nm.
10. The method for preparing the composite nano-filtration material according to any one of claims 7 to 9, characterized in that: The first solvent includes one or more of dimethylformamide, ethanol, dichloromethane, and dimethylformamide; The second solvent includes one or more of dimethylformamide, dimethylformamide, dimethyl sulfoxide, ionic liquid, N-methylpyrrolidone, dichloromethane, chloroform, and acetic acid.
Citation Information
Patent Citations
Method for preparing tea polyphenol / cellulose acetate nanofiber membrane
CN105220361A
Tea polyphenol cellulose fiber and preparation method thereof
CN106521671A
High-filtration type nano melt-blown cloth and manufacturing process thereof
CN112026281A
Modified melt-blown polypropylene composite filter material and preparation method thereof
CN112354267A
Silicon dioxide aerogel modified melt-blown polypropylene antibacterial material and preparation method thereof
CN113332793A
Cited By
Composite nanofiber filter material preparation device and process thereof
CN120515294A